Kesiapan Berwirausaha Mahasiswa program Studi Pendidikan Kesejahteraan Keluarga Universitas Negeri Padang - Widia Wahyuni; Elida Elida (STKIP PGRI SITUBONDO, 2023)
Many factors cause unemployment among students who have completed their education in Indonesia, one of which is the lack of entrepreneurial readiness to start a business. The purpose of this research is to describe the entrepreneurial readiness of students of the Padang State University family welfare education study program based on indicators of mental entrepreneurial readiness, entrepreneurial knowledge readiness, and entrepreneurial skill readiness. 142 students who became the research population and 59 students who became the research. The data analysis technique was carried out using descriptive analysis using the method of categorizing the assessment based on the average score and percentage. The results showed that students' entrepreneurship readiness indicators were in the medium category, entrepreneurship knowledge readiness indicators were in the less category, and entrepreneurship skill readiness indicators were in the medium category. Based on the results of the study it can be concluded that the readiness of entrepreneurship owned is not enough to foster student entrepreneurship readiness.